Positive and negative parenting in conduct disorder with high versus low levels of callous–unemotional traits. (August 2021) - Pauli, Ruth; Tino, Peter; Rogers, Jack C.; Baker, Rosalind; Clanton, Roberta; Birch, Philippa; Brown, Abigail; Daniel, Gemma; Ferreira, Lisandra; Grisley, Liam; Kohls, Gregor; Baumann, Sarah; et al.
Abstract: Less is known about the relationship between conduct disorder (CD), callous–unemotional (CU) traits, and positive and negative parenting in youth compared to early childhood. We combined traditional univariate analyses with a novel machine learning classifier (Angle-based Generalized Matrix Learning Vector Quantization) to classify youth ( N = 756; 9–18 years) into typically developing (TD) or CD groups with or without elevated CU traits (CD/HCU, CD/LCU, respectively) using youth- and parent-reports of parenting behavior. At the group level, both CD/HCU and CD/LCU were associated with high negative and low positive parenting relative to TD. However, only positive parenting differed between the CD/HCU and CD/LCU groups. In classification analyses, performance was best when distinguishing CD/HCU from TD groups and poorest when distinguishing CD/HCU from CD/LCU groups. Positive and negative parenting were both relevant when distinguishing CD/HCU from TD, negative parenting was most relevant when distinguishing between CD/LCU and TD, and positive parenting was most relevant when distinguishing CD/HCU from CD/LCU groups. These findings suggest that while positive parenting distinguishes between CD/HCU and CD/LCU, negative parenting is associated with both CD subtypes. These results highlight the importance of considering multiple parenting behaviors in CD with varying levels of CU traits in late childhood/adolescence.